Indonesia's Digital Economic Policy To Increase Economic Resilience - Muhamad Samingan; Lukman Yudho Prakoso; Suwito, Suwito (CV. AFDIFAL MAJU BERKAH, 2024)
The growth of information and communication technology (ICT) has changed the way people live their lives and conduct business. The era of the Industrial Revolution 4.0, characterized by the use of digital technology and the Internet of Things (IoT), has created a new economic environment known as the “digital economy.